2017
DOI: 10.1371/journal.pone.0171143
|View full text |Cite|
|
Sign up to set email alerts
|

Zebrafish atoh8 mutants do not recapitulate morpholino phenotypes

Abstract: Atoh8 is a bHLH transcription factor expressed in pancreas, skeletal muscle, the nervous system, and cardiovascular tissues during embryological development. Although it has been implicated in the regulation of pancreatic and endothelial cell differentiation, the phenotypic consequences of Atoh8 loss are uncertain. Conclusions from knockout studies in the mouse differ widely depending on the targeting strategy used, while atoh8 knockdown by interfering morpholino oligonucleotides (morpholinos) in zebrafish has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
1
18
1
Order By: Relevance
“…We have identified compensation triggered by a mutation in actc1b but not following morpholino mediated knockdown of Actc1b. There has been considerable debate recently as a result of phenotypic differences between mutant lines and morpholino-mediated knockdown [ 19 22 ]. The study by Rossi et al (2015) provided an example where this difference in phenotype was due to compensation, rather than morpholino off target effects as previously suggested.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified compensation triggered by a mutation in actc1b but not following morpholino mediated knockdown of Actc1b. There has been considerable debate recently as a result of phenotypic differences between mutant lines and morpholino-mediated knockdown [ 19 22 ]. The study by Rossi et al (2015) provided an example where this difference in phenotype was due to compensation, rather than morpholino off target effects as previously suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepant mutant and morphant phenotypes have been reported for an ever-increasing number of genes, raising several caveats about the use of MOs [ 49 ] [ 50 ] [ 51 ] [ 52 ] [ 53 ] [ 54 ]. Explanations to account for MOs not replicating null-mutant phenotypes include off-target/non-specific effects of MOs, unexpected changes in gene expression, and apoptosis via a p53-dependent mechanism [ 55 ] [ 49 ] [ 50 ] [ 51 ] [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two types of cldn5a morphants showed similar phenotypes of disrupted heart laterality and exogenous RNA rescued the cldn5a morpholino-induced phenotypes. Several recent papers reported that genome-engineered mutants failed to recapitulate the morpholino-induced phenotypes [ 54 56 ]. Although genetic compensation might be induced in mutant embryos [ 57 ], morpholino-based studies should be carefully considered whether their phenotypes are driven by off-target effects.…”
Section: Discussionmentioning
confidence: 99%